The HIV epidemic in Colombia: spatial and temporal trends analysis - Jhon Freddy Montana; Glenda Roberta Oliveira Naiff Ferreira; Carlos Leonardo Figueiredo Cunha; Ana Angélica Rêgo de Queiroz; Wellington Augusto Andrade Fernandes; Sandra Helena Isse Polaro; Lucia Hisako Takase Gonçalves; Danielle Costa Carrara Couto; Elucir Gir; Renata Karina Reis; Wiliam Sorensen; Eliã Pinheiro Botelho (BMC, 2021)
Abstract Background Colombia has the fourth highest incidence rate of HIV/AIDS among all Latin American countries and it has been increasing since the 1980s. However, the number of studies that addresses this trend is limited. Here, we employed spatial and temporal trend analyses to study the behaviour of the epidemic in the Colombian territory. Methods Our sample included 72,994 cases of HIV/AIDS and 21,898 AIDS-related deaths reported to the National Ministry of Health between 2008 and 2016. We employed the joinpoint regression model to analyse the annual HIV/AIDS incidence and AIDS mortality rates. In the spatial analysis, we used univariate autocorrelation techniques and the Kernel density estimator. Results While the HIV/AIDS incidence had an increasing trend in Colombia, the AIDS mortality rate was stable. HIV/AIDS incidence and AIDS mortality showed a downward trend in the 0-14 age group. An upward trend was observed for HIV/AIDS incidence in people older than 15 years and with the highest trend in the 65 years and above group. AIDS mortality showed an increasing trend among people aged 65 years or older. The comparison between the sexes showed an upward trend of HIV/AIDS incidence in all age groups and AIDS-mortality rates in 65 years and above in men, while in women, the incidence was upward among those aged 45 years and above, and concerning the AIDS-mortality rate in the 45-64 group. The high-high clusters of HIV/AIDS incidence and AIDS mortality were located in the Andean and Caribbean regions. Conclusion Our study found an upward trend in HIV/AIDS incidence and a stable trend in the AIDS mortality rate in Colombia. The downward trend in HIV/AIDS incidence and AIDS mortality rate in the 0-14 age group reflects the downwards mother-to-child HIV transmission. The upward trend in HIV/AIDS incidence in older women and AIDS mortality in younger women rates, compared with men, may be due to late diagnosis and treatment. The Caribbean and the 'coffee belt' regions were the most impacted by the HIV epidemic, most likely due to sexual tourism. Our results provide crucial information that may help Colombian health authorities fight HIV transmission.